Tool Path of Air Time Motion in Pocket Milling by Biogeogra-phy-Based Optimization (BBO) - Narooei, Khashayar Danesh; Ramli, Rizauddin; Hishamuddin, Hawa; Pasla, Shahla; Ghasimi, Salah Alden; Tamjidy, Mehran (International Journal of Engineering and Technology, 2018)
The milling process is one of the most commonly metal-cutting processes in the industry because of its ability to remove material faster with desirable surface quality. Thus, it is applicable in a variety of manufacturing industries such as automotive and aerospace, where the production time is an important factor in yield parts. This paper presents a new method of biogeography-based optimization (BBO) to determine the optimal airtime motion in computer numerical control (CNC) milling process. The optimization of airtime motion is formulated as a Traveling Salesman problem (TSP). Furthermore, the result of the simulation using our developed BBO is compared with the random machining process. Consequently, the BBO averagely determined 55.62 percent optimum airtime motion rather than random machining process. The optimal tool path obtained is later tested in pocket milling process in CNC milling machine. It can be ascertained that the developed optimization model for airtime motion can be utilized for the specified product area.